2021
DOI: 10.3390/biomedicines9111659
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Critical Biomarkers of Major Depressive Disorder: A Comprehensive Perspective

Abstract: Major Depressive Disorder (MDD) represents a major global health concern, a body-mind malady of rising prevalence worldwide nowadays. The complex network of mechanisms involved in MDD pathophysiology is subjected to epigenetic changes modulated by microRNAs (miRNAs). Serum free or vesicles loaded miRNAs have starred numerous publications, denoting a key role in cell-cell communication, systematically and in brain structure and neuronal morphogenesis, activity and plasticity. Upregulated or downregulated expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 279 publications
0
22
0
Order By: Relevance
“…The modifications that cause those events can be mediated by DNA methylation, histone modification, and also the expression of signaling non-coding RNAs, mainly represented by long-noncoding RNAs (lncRNAs) and microRNAs (miRNAs) ( 23 25 ). That epigenetic regulation can occur not only from nervous system development but also in the mature brain with long-lasting effects and the possibility to be heritable for multiple generations ( 26 ).…”
Section: Epigenetic Basis Of Mddmentioning
confidence: 99%
See 2 more Smart Citations
“…The modifications that cause those events can be mediated by DNA methylation, histone modification, and also the expression of signaling non-coding RNAs, mainly represented by long-noncoding RNAs (lncRNAs) and microRNAs (miRNAs) ( 23 25 ). That epigenetic regulation can occur not only from nervous system development but also in the mature brain with long-lasting effects and the possibility to be heritable for multiple generations ( 26 ).…”
Section: Epigenetic Basis Of Mddmentioning
confidence: 99%
“…These changes can lead to maladaptive neuronal plasticity, poorer resilience to stress, depressive mood, and different response to antidepressants ( 27 ). Recent work reviews have denoted the lack of information regarding the validation of depression-associated epigenetic modifications due to the short age of this field of study, the small sample size of patients, and the difficulties to study functioning changes in alive brains instead of postmortem ( 23 ), although there are some epigenetic markers that could be studied in serum and body fluids such as miRNAs ( 25 ). Besides, sometimes it is not possible to establish a clear causality of the epigenetic findings because of the difficulty of replicate the experimental results from animals to humans ( 28 ).…”
Section: Epigenetic Basis Of Mddmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the miR-29b-3p expression levels in the CSF were significantly higher in depressed patients than they were in the control subjects, suggesting the involvement of increased miR-29b expression in depression-related AAA development. Compared to miRNA-29b, the miRNA-146a expression level in patients with MMD has been studied more extensively [ 43 , 44 ]. Hung et al showed that the miRNA-146a levels in the peripheral blood monocytes from MDD patients were significantly lower than they were in healthy controls, which was partially restored after antidepressant treatment [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two central mechanisms should be highlighted to understand the anti-depressant effect of SCFAs: (1) epigenetic regulation and (2) immunomodulatory action. Depressed patients show a prominent epigenetic footprint in comparison to non-depressed subjects, including critical alterations in DNA methylation, histone modifications, and non-coding RNAs (i.e., microRNAs) [90][91][92]. SCFAs act as histone deacetylases (HDAC) inhibitors, playing a key role in the DNA methylation, histone modification, and chromatin restructuring to alter gene expression [93].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%